Socioeconomic status and self-reported tuberculosis: a multilevel analysis in a low-income township in the Eastern Cape, South Africa - Jane Murray Cramm; Xander Koolman; Valerie Møller; Anna P. Nieboer (AOSIS, 2011)
Few studies have investigated the interplay of multiple factors affecting the prevalence of tuberculosis in developing countries. The compositional and contextual factors that affect health and disease patterns must be fully understood to successfully control tuberculosis. Experience with tuberculosis in South Africa was examined at the household level (overcrowding, a leaky roof, social capital, unemployment, income) and at the neighbourhood level (Gini coefficient of inequality, unemployment rate, headcount poverty rate). A hierarchical random-effects model was used to assess household-level and neighbourhood-level effects on self-reported tuberculosis experience. Every tenth household in each of the 20 Rhini neighbourhoods was selected for inclusion in the sample. Eligible respondents were at least 18 years of age and had been residents of Rhini for at least six months of the previous year. A Kish grid was used to select one respondent from each targeted household, to ensure that all eligible persons in the household stood an equal chance of being included in the survey. We included 1020 households within 20 neighbourhoods of Rhini, a suburb of Grahamstown in the Eastern Cape, South Africa. About one-third of respondents (n=329; 32%) reported that there had been a tuberculosis case within the household. Analyses revealed that overcrowding (P≤0.05) and roof leakage (P≤ 0.05) contributed significantly to the probability of a household TB experience, whereas higher social capital (P≤0.01) significantly reduced this probability. Overcrowding, roof leakage and the social environment affected tuberculosis prevalence in this economically disadvantaged community. Policy makers should consider the possible benefits of programs that deal with housing and social environments when addressing the spread of tuberculosis in economically poor districts.